Collection Development at Two Armenian University Libraries: A Conversation with Librarians and Faculty - Aram Donabedian, D.; Carey, John; Balayan, Arshak (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2020)
In the summer of 2016 two Hunter College librarians, working with a colleague in the Republic of Armenia, conducted an IRB-approved focus group at the American University of Armenia in Yerevan, Armenia.  This group drew participants from the libraries and other academic departments of the American University of Armenia as well as Yerevan State University, a large public institution.  The discussion attempted to ascertain whether these libraries have devised effective strategies to acquire materials and build collections in the face of the challenges they face (budgetary, linguistic, and sometimes political) and whether faculty at these institutions feel their library’s collection meets their teaching and research needs.  Together with results from an online survey, the responses gathered help illuminate the challenges that scholars and librarians face in the unique context of the South Caucasus, as Armenia and other countries in the region continue to develop post-Soviet models of higher education and transition to more democratic forms of government.